Aqueous Extract of Lycium ruthenicum Murray Attenuates Neuroinflammation in C57BL/6J Mice Induced by High-Fat and High-Fructose Diet Through Regulating Gut Microbiota and Bile Acid Metabolism - Xia Fan; Wei Dong; Yujie Huang; Yifan Shu; Yamei Yan; Jia Mi; Lu Lu; Xiaoxiong Zeng; Youlong Cao (Foods)
The aqueous extract of Lycium ruthenicum Murray (LRE) could attenuate neuroinflammation in mice induced by a high-fat and high-fructose diet (HFFD). Moreover, LRE could adjust bile acid (BA) metabolism and the gut microbiota. Behavioral tests revealed that LRE prevented HFFD-induced cognitive deficits. The treatment of LRE resulted in a decreased expression of inflammation-related mRNA of TNF-α, IL-6, and IL-1β in the cerebral cortex and hippocampus. Furthermore, LRE ameliorated gut microbiota disorder caused by HFFD by markedly elevating the relative abundances of Streptococcus and probiotics such as Lactococcus. Concurrently, it reduced the relative abundances of Helicobacter and Clostridium_XIVa. The levels of tauroursodeoxycholic acid, known for its neuroprotective property, and taurocholic acid, recognized as an anti-inflammatory agent, were significantly enhanced in the hippocampus and cerebral cortex due to the treatment with LRE. In a word, LRE might have the potential to alleviate HFFD-induced cognitive dysfunction by modulating intestinal microbiota and promoting the synthesis of neuroprotective BAs.